Molecular docking and molecular dynamics to identify collagenase inhibitors as lead compounds to address osteoarthritis. Issue 5 (24th March 2022) - Roy, Himadri Shekhar; Dubey, Gurudutt; Sharma, Vishnu Kumar; Bharatam, Prasad V.; Ghosh, Deepa
Abstract: Osteoarthritis (OA) is a degenerative disease which affects a large number of individuals. Collagenases, which belong to a class of metalloproteases (MMPs), are responsible for the degradation of cartilage manifested in OA. Inhibition of the catalytic domains of these MMPs is one of the important therapeutic strategies proposed for the prevention of OA. The main objective of this work is to evaluate the binding of curcumin and its metabolites with the active sites of collagenases in comparison to standard inhibitors on the basis of our hypothesis that curcumin/metabolites could exhibit an inhibitory effect on MMPs. Here, we report the molecular docking analysis of curcumin and its metabolites with collagenases (MMP-1, MMP-8, MMP-13). Among the molecules tested, curcumin monoglucuronide (CMG) demonstrated the best binding affinity with MMP-13, which is specifically implicated in OA. The CMG–MMP-complexes were further subjected to molecular dynamic simulations to explore the stability of the complexes and to estimate the free binding energies. The results indicated that CMG preferentially bind to MMP-13 in comparison to that of MMP-1 and MMP-8 with binding free energies (ΔGbind ) of (−60.55), (−27.02) and (−46.91) kcal/mol, respectively. This is the first study which suggests that curcumin monoglucuronide can be considered as an effective lead compound to prevent the progression of OA. Communicated by Ramaswamy H. Sarma